Penerapan Jurnalisme Gonzo di Highvolta Media - Muhammad Taufik; Doddy Iskandar (UNISBA Press, 2022)
Abstract. This study focuses on explaining the implementation of Gonzo journalism in an alternative media, namely Highvolta Media. Pioneered by Hunter S. Thompson, gonzo journalism produces stories tailored to the needs of a mix of the skills of a good journalist, the eye of a photographer or artist, and the field skills of a photographer. It is this flow of gonzo journalism that Highvolta Media is trying to make as a basis for carrying out its duties as a reporter and also applying it to the newsroom to carry out every journalistic activity that occurs at Highvolta Media. This study aims to determine how the implementation of gonzo journalism at Highvolta Media. This study uses a qualitative method with a case study research approach. In this case, the researcher tries to find out the reasons and how the journalistic practices that occur at Highvolta Media with the use of gonzo journalism. Also finding out how relevant Gonzo journalism is to its subjectivity in the world of journalism. The results of the study revealed that Highvolta Media had inadvertently applied gonzo journalistic characteristics to their writing style from the beginning, but was not known by its members. It was realized by them when their second year was running. gonzo journalism was finally implemented and Highvolta Media gained an ever-increasing readership. Abstrak. Penelitian ini berfokus pada pemaparan implementasi jurnalisme gonzo di sebuah media alternatif, yaitu Highvolta Media. Dipelopori oleh Hunter S. Thompson, jurnalisme gonzo dalam menghasilkan berita yang ditulis secara subjektif membutuhkan campuran antara kemampuan seorang wartawan yang baik, mata seorang fotografer atau seniman, dan kemampuan lapangan bak seorang aktor. Aliran jurnalisme gonzo inilah yang dicoba oleh Highvolta Media untuk dijadikan sebagai landasan dalam melaksanakan tugas sebagai pewarta dan juga menerapkannya pada ruang redaksi untuk menjalankan setiap kegiatan jurnalistik yang terjadi di Highvolta Media. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan jurnalisme gonzo di Highvolta Media. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan penelitian studi kasus. Dalam hal ini peneliti berusaha mencari tahu alasan dan bagaimana praktik jurnalistik yang terjadi di Highvolta Media dengan penggunaan jurnalisme gonzonya. Juga mencari tahu bagaimana relevansi jurnalisme gonzo yang kental akan unsur subjektivitasnya di dunia kejurnalistikan. Hasil penelitian mengungkapkan bahwa Highvolta Media secara tidak sengaja dari awal terbentuknya sudah menerapkan karakteristik-karakteristik jurnalisme gonzo pada gaya penulisan mereka, namun tidak diketahui oleh para anggotanya. Disadari oleh mereka ketika tahun kedua mereka berjalan. jurnalisme gonzo akhirnya berhasil diterapkan dan Highvolta Media mendapatkan pembaca yang semakin meningkat jumlahnya.